FeCo2O4 submicron-tube arrays grown on Ni foam as high rate-capability and cycling-stability electrodes allowing superior energy and power densities with symmetric supercapacitors. Issue 12 (11th January 2016) - Zhu, Baogang; Tang, Shaochun; Vongehr, Sascha; Xie, Hao; Zhu, Jian; Meng, Xiangkang
Abstract : Homogeneous FeCo2 O4 submicron-tube arrays grown on Ni foam as binder-free electrodes allow even symmetric devices to have superior energy densities. Abstract : Template-free chemical growth on Ni foam and thermal treatment results in homogeneous FeCo2 O4 submicron-tube arrays which serve as binder-free electrodes with high capacitance, rate-capability and cycling-stability owing to FeCo2 O4 conductivity, high porosity, and strong bonding between tubes and Ni foam, all allowing even symmetric devices to have superior energy density.